Improved satellite-derived PV power nowcasting using real-time power data from reference PV systems. (1st July 2018) - Bright, Jamie M.; Killinger, Sven; Lingfors, David; Engerer, Nicholas A.
Highlights: We demonstrably improve real-time PV power nowcasting. We evaluate different methods of real-time nowcasting. We report success at deriving PV-DG power estimates in the LV grid. We report up to 90.5% reduction in error metrics with the new methodology. Abstract: Rapid growth in the global penetration of solar photovoltaic (PV) systems means electricity network operators and electricity generators alike are increasingly concerned with the short-term solar forecasting (nowcasting) of solar irradiance. This paper proposes a methodology that considers a varying number of available reference PV systems for supporting satellite-derived PV power real-time nowcasting. We evaluate conventional satellite-only and upscaling-only PV fleet estimate methodologies and compare them to two newly developed correction and hybrid cases. When using only a single reference PV system to estimate the aggregated power of 48 independent target PV systems for the location of Canberra, Australia; we show that the newly proposed correction or hybrid cases improve the performance of the satellite-derived PV power estimate medians in terms of MBE, rMBE, RMSE and rRMSE from 0.031  W / W p, 7.46 %, 0.079  W / W p and 23.4 %, down to 0.006  W / W p, - 0.711 %, 0.068  W / W p and 20.0 %, representing relative improvements of 80.6%, 90.5%, 13.9% and 14.5%, respectively. Similarly, when using 30 reference PV systems, we report median improvements from 0.036  W / W p, 8.25 %, 0.083  W / W p and 24.8 %, down to 0.01  W / W p, 1.41 %, 0.049  W / W p and 11.4 %, representing relative improvements of 72.2%, 82.9%, 41.0% and 54.0%, respectively. We discuss the fundamental challenges facing the use of reference PV systems, satellite-derived power estimates, combining the two data sources, and the knowledge required to address these issues. We ultimately conclude that combining satellite-based PV power estimates with data from reference PV systems is always more beneficial than either on their own.